Determinants of Musculoskeletal Disorders among Small-Scale Textile Workers: A Cross Sectional Study - Subhajit Shyam; Rekha Dutt (Medsci Publications, 2017)
Introduction: Empirical evidence suggest that the workers in the garment units suffer from work related musculoskeletal disorders such as carpel tunnel syndrome, forearm tendinitis, epicondilitis, bicapital tendinitis, lower back pain, neck pain, shoulder pain and osteoarthritis of the knee. Therefore the present study was undertaken to find out the determinants leading to musculoskeletal disorders among the small scale textile workers. Methodology: A community based, cross-sectional study was conducted among the small-scale textile workers of Meerut. The subjects were interviewed and examined as per a pre-designed, pre-tested semi-structured interview questionnaire. Result: There was significant relation between age, years and hours of working and marital status with musculoskeletal disorders. Around 70% of workers having history of addiction developed musculoskeletal disorders. Conclusion: A highly significant association between increasing age, more years of work experience, and more hours of work per day, addiction, marital status and musculoskeletal disorders was seen in the study.